2016
DOI: 10.1371/journal.pone.0162766
|View full text |Cite
|
Sign up to set email alerts
|

PERK Regulates Working Memory and Protein Synthesis-Dependent Memory Flexibility

Abstract: PERK (EIF2AK3) is an ER-resident eIF2α kinase required for memory flexibility and metabotropic glutamate receptor-dependent long-term depression, processes known to be dependent on new protein synthesis. Here we investigated PERK’s role in working memory, a cognitive ability that is independent of new protein synthesis, but instead is dependent on cellular Ca2+ dynamics. We found that working memory is impaired in forebrain-specific Perk knockout and pharmacologically PERK-inhibited mice. Moreover, inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Interestingly, genetic silencing of PERK in tested animals has also been performed with similar results [261]. A recent study by Zhu et al has also found that inhibition of PERK with GSK2606414 affects working memory, as mice treated with the inhibitor appeared to be impaired in a spontaneous alternation Y-maze task as well as in fear extinction, which implies the impairment of spatial working memory and memory flexibility, respectively [262]. Lastly, Sharma et al reported that reduction of PERK expression by GSK2606414 improved hippocampal-dependent memory and learning, as well as increasing neuronal excitability after injection into the CA1 region in middle-aged mice.…”
Section: Gsk2606414mentioning
confidence: 59%
“…Interestingly, genetic silencing of PERK in tested animals has also been performed with similar results [261]. A recent study by Zhu et al has also found that inhibition of PERK with GSK2606414 affects working memory, as mice treated with the inhibitor appeared to be impaired in a spontaneous alternation Y-maze task as well as in fear extinction, which implies the impairment of spatial working memory and memory flexibility, respectively [262]. Lastly, Sharma et al reported that reduction of PERK expression by GSK2606414 improved hippocampal-dependent memory and learning, as well as increasing neuronal excitability after injection into the CA1 region in middle-aged mice.…”
Section: Gsk2606414mentioning
confidence: 59%
“…It would be quite instructive if some additional work on PERK and JNK in the context of memory formation/Learning could be added here. Specifically, I am thinking of the work of Zhu S et al, 2016, Plos One; and Ounallah-Saad et al in JNeuroscience. Both papers report on the cognitive benefits of a lowering of PERK by either genetic or pharmacological means.…”
Section: Responsementioning
confidence: 99%
“…"Interestingly, despite the superior performance of genetically deficient PERK mice in behavioural tasks that require protein synthesis for learning , such mice demonstrated reduced working memory in several tasks known to be independent of protein synthesis. The latter may indicate an additional role of PERK in the regulation Ca 2+ dynamics (Zhu et al, 2016)". 4.…”
Section: Replymentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological inhibition or genetic inactivation of another eIF2 kinase, PERK, was shown to improve cognitive functions (Zhu et al, 2016) but PERK-KO mice develop pancreatic dysfunction that might represent serious liability for PERK inhibitors (Harding et al, 2001). Pharmacological inhibition of PKR with the small molecule C16 was also shown to enhance cognitive performance in wild type mice (Ingrand 2007;Stern 2013;Zhu 2011) and to reverses deficits in ApoE4-Ki (Segev et al, 2015) but C16 lacks potency and selectivity versus other eIF2AKs and other kinases (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%